O-001 Impact of Recanalization in Patients with Pretreatment DWI-ASPECTS ≤6 Treated with Endovascular Therapy. (29th July 2016) - Desilles, J; Consoli, A; Escalard, S; Redjem, H; Blanc, R; Guedin, P; Coskun, O; Ciccio, G; Smajda, S; Ruiz Guerrero, C; Sasannejad, P; Rodesch, G; et al.
Abstract : Background and purpose: In acute ischemic stroke (AIS) patients, a diffusion-weighted imaging (DWI) Alberta Stroke Program Early Computed Tomography Score (ASPECTS) is correlated with infarct volume and is an independent factor of functional outcomes. Patients with pretreatment DWI-ASPECTS ≤6 were excluded or underrepresented in the recent randomized endovascular therapy (EVT) trials. Our aim was to assess the impact of recanalization in patients with pretreatment DWI-ASPECTS ≤6 treated with EVT. Methods: We analyzed data collected between January 2012 and August 2015 in 2 prospective clinical registries of AIS patients treated with EVT. Every patient with a documented internal carotid artery or middle cerebral artery occlusion with pretreatment DWI-ASPECTS ≤6 was eligible for this study. The primary outcome was a favorable outcome defined by a modified Rankin Scale of 0 to 2 at 90 days. Results: Two hundred eighteen patients were included. Among them, 145 (66%) had a good recanalization (TICI ≥ 2 b) at the end of EVT. There was no statistically difference in the baseline clinical characteristics between recanalised and non-recanalised patients. Recanalized patients had an increased rate of favorable outcomes (38.7% vs 17.4%, p = 0.002) and a decreased rate of mortality at 3 months (22.5% vs 39.1%, p = 0.013) compared with non-recanalised patients. The symptomatic intracerebral hemorrhage rate was not different in the 2 groups (13% vs 14.1%, p = 0.83). Conclusion: Patients with a pretreatment DWI-ASPECTS ≤6 may still benefit of EVT when a good recanalization is achieved. In particular, EVT-induced recanalization was associated with a reduced rate of mortality without increased risk of symptomatic intracerebral hemorrhage. Disclosures: J. Desilles: None. A. Consoli: None. S. Escalard: None. H. Redjem: None. R. Blanc: None. P. Guedin: None. O. Coskun: None. G. Ciccio: None. S. Smajda: None. C. Ruiz Guerrero: None. P. Sasannejad: None. G. Rodesch: None. M. Piotin: None. B. Lapergue: None.